Effect of Cord Blood Low Molecular Fraction on Adenylate Metabolism in Leukoconcentrate Cells after Cryopreservation - Akhatova, Yu. S.; Sysoyev, A. A.; Sysoyeva, I. V.; Gulevsky, A. K. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):180.